Seed management and selection in ancient maize landraces from the French Pyrenees: ethnobotanical survey and selection experiment - Brigitte Gouesnard; Yacine Diaw; Laurène Gay; Joëlle Ronfort; Jacques David (Genetic Resources and Crop Evolution, 2025)
Maize landraces ( Zea mays subsp. mays ) have evolved under the joint action of environmental factors and of the farmers who cultivated them. In this study, we aim to quantify the selection gradients exerted by farmers by proposing them a selection test consisting in choosing the ears they would select if they were to grow maize landraces the following year. The study focused on the Pyrenees region of France, where landraces were cultivated until the arrival of hybrids in the 1960s and conserved ex-situ ever since. We interviewed former Pyrenean farmers or their children who were cultivating landraces 60 years ago. The survey documented seed management practices and know-how. Our selection test showed that their selection was based solely on ears: old farmers selected healthy and productive ears by using ear length and volume as the first two selection criteria. Both were highly correlated with the kernel weight per ear. Heritabilities of ear traits at an individual plant level were estimated in one trial for four landraces and were found variable between traits and landraces (average 0.36 ranging between 0 and 0.76). We calculated the expected genetic change after one generation of mass selection, following farmer selection criteria. For ear length, genetic change was expected to reach about 3.4% (from 1 to 7.5% over the 17 selection tests). We investigated seed selection practices both east and west of the Pyrenees and compared them qualitatively with those of native American farmers.

Genotyping-by-sequencing highlights original diversity patterns within a European collection of 1191 maize flint lines, as compared to the maize USDA genebank - Brigitte Gouesnard; Sandra Negro; Amélie Laffray; Jeff Glaubitz; Albrecht Melchinger; Pedro Revilla; Jesus Moreno-Gonzalez; Delphine Madur; Valérie Combes; Christine Tollon-Cordet; Jacques Laborde; Dominique Kermarrec; et al. (Theoretical and Applied Genetics, 2017)

Expression on roots and contribution to maize phytostimulation of 1-aminocyclopropane-1-decarboxylate deaminase gene acdS in Pseudomonas fluorescens F113 - Jordan Vacheron; Emeline Combes-Meynet; Vincent Walker; Brigitte Gouesnard; Daniel Muller; Yvan Moënne-Loccoz; Claire Prigent-Combaret (Plant and Soil, 2016)

Identification of adaptation traits to drought in collections of maize landraces from southern Europe and temperate regions - Brigitte Gouesnard; Anne Zanetto; Claude Welcker (Euphytica, 2016)

Is diversification history of maize influencing selection of soil bacteria by roots? - MARIE‐LARA BOUFFAUD; MARTINA KYSELKOVÁ; BRIGITTE GOUESNARD; GENEVIEVE GRUNDMANN; DANIEL MULLER; YVAN MOËNNE‐LOCCOZ (Molecular Ecology, 2012)
A wide range of plant lines has been propagated by farmers during crop selection and dissemination, but consequences of this crop diversification on plant‐microbe interactions have been neglected. Our hypothesis was that crop evolutionary history shaped the way the resulting lines interact with soil bacteria in their rhizospheres. Here, the significance of maize diversification as a factor influencing selection of soil bacteria by seedling roots was assessed by comparing rhizobacterial community composition of inbred lines representing the five main genetic groups of maize, cultivated in a same European soil. Rhizobacterial community composition of 21‐day‐old seedlings was analysed using a 16S rRNA taxonomic microarray targeting 19 bacterial phyla. Rhizobacterial community composition of inbred lines depended on the maize genetic group. Differences were largely due to the prevalence of certain Betaproteobacteria and especially Burkholderia , as confirmed by quantitative PCR and cloning/sequencing. However, these differences in bacterial root colonization did not correlate with plant microsatellite genetic distances between maize genetic groups or individual lines. Therefore, the genetic structure of maize that arose during crop diversification (resulting in five main groups), but not the extent of maize diversification itself (as determined by maize genetic distances), was a significant factor shaping rhizobacterial community composition of seedlings.

Analysis of photoperiod sensitivity within a collection of tropical maize populations - Brigitte Gouesnard; Cécile Rebourg; Claude Welcker; Alain Charcosset (Genetic Resources and Crop Evolution, 2002)